Developing and Evaluating the Effectiveness of a Nursing Leadership Mentoring Pilot Program. Issue 2 (9th April 2023) - Hedenstrom, Margot L.; Spiva, LeeAnna; Thurman, Susan; Hale, Regina L.; Toney, Sharlene; Case-Wirth, Jill; Kairu, Mumbi; Sneha, Sweta
Abstract : The nurse leader role is a vital role in ensuring quality, safety, and staff retention in the health care setting. A new nurse manager often receives little mentoring support when assuming a new role. Fifteen mentor/mentee pairs were provided with 6 training sessions specifically designed using the Hale Mentoring Up theoretical framework. Surveys and focus groups were conducted at mid- and endpoints. Data were digitally recorded, transcribed verbatim, and loaded into NVivo 12. Two attributes that facilitated a positive mentoring relationship emerged from the qualitative analysis: interpersonal and organizational skills. Interpersonal skills included a mentor-mentee relationship that was built upon trust, flexibility, and learning and development; and organizational skills included building relationships both internally and externally. Furthermore, time was identified as a barrier to mentoring. A mentoring program is a vehicle to help support new nurse leaders through an educational intervention and mentoring support program. The development of a mentoring pilot program helps to strengthen future nursing leadership to support new leaders in their roles.